Plasticity in the Brainstem: Prenatal and Postnatal Experience Can Alter Laterodorsal Tegmental (LDT) Structure and Function - Kohlmeier, Kristi A.; Polli, Filip S. (Frontiers in Synaptic Neuroscience, 2020)
The brainstem has traditionally been considered an area of the brain with autonomous control of mostly homeostatic functions, which would preclude the necessity to exhibit the high degree of synaptic or cellular mechanisms of plasticity typical of regions of the brain responsible for flexible executive control, such as the medial prefrontal cortex or the hippocampus. The perception that the brainstem exhibits a lack of ability to change synaptic strength and/or wiring within local circuits makes intuitive sense, as it is not easy to understand how 'soft wiring' would be an advantage when considering the importance of faithful and consistent performance of homeostatic autonomic functions which are controlled by the brainstem, such as heart rate, respiration, or state control. However, many of the molecular and cellular requirements which underlie strengthening of synapses seen in brain regions involved in higher-level processing are present in brainstem nuclei, and recent research suggest that the view of the brainstem as 'hard wired', with rigid and static connectivity and with unchanging synaptic strength, is outdated. In fact, information from studies within the last decades, including work conducted in our group, leads us to propose that the brainstem can dynamically alter synaptic proteins and change synaptic connections in response to stimuli, and this would likely alter functionality and output. In addition, the brainstem can develop differently in response to environmental elements present during the prenatal period. Evidence exists that exposure of the brain during gestation to drugs of abuse can result in quite different alterations in the brainstem, than would similar exposures occurring during the juvenile period or adulthood. This article reviews recent research that has provided information resulting in our revision of the view of the brainstem as static and non-changing by using as example recent information gleaned from a brainstem pontine nucleus, the laterodorsal tegmentum (LDT), which has demonstrated mechanisms of synaptic plasticity as well as differential development if nicotine is present during the gestational period.